Integrasi Turāth Dalam Pendidikan Islam Kontemporer: Analisis Konseptual Adab, Spiritualitas, dan Karakter Berbasis Pemikiran Klasik - Abdulloh Arif Mukhlas; Sutono; Mulyadi; Ahmad Qomari; Saiful Anfiroh; Siti Aliyah; Nurul Hidayah; Moch. Samsul Anwar; Moh. Qosim; Muhammad Abdul Mukid; Yulianah; Muhammad Abdul Ghofur; Nuriyati; Moh. Habibur Rachman; Sulistiana; Achmad (Jurnal Pendidikan Agama Islam Miazhar, 2026)
Integration of turāth thought as the foundation of contemporary character education through a study of the concepts of adab, spirituality, and character formation in the monumental works of classical scholars. The research method uses a qualitative approach with a library research design and hermeneutic content analysis of primary texts including Ta'lim al-Muta'allim (Az-Zarnuji), Ayyuha al-Walad (Al-Ghazali), and Al-Muqaddimah (Ibn Khaldun), as well as relevant secondary sources. The results of the study indicate that turāth offers a holistic pedagogical-therapeutic framework by emphasizing the integration of intellectual, moral, and spiritual dimensions. Az-Zarnuji's concept of adab places ethics as the foundation of academic success; Al-Ghazali's thoughts on tazkiyah al-nafs provide a character formation model based on heart therapy (takhliyah-tahliyah); while Ibn Khaldun offers an educational paradigm based on social reality ('umrān and 'asabiyyah). Contextualization of turāth through the Maqāṣid al-Syarī'ah, historical-critical, and digitalization approaches produces contemporary learning models such as Contextual Teaching and Learning (CTL), Project-Based Learning (PjBL), and ServiceLearning that are relevant to the needs of modern Islamic education. Therefore, the integration of turāth is able to address the character crisis and loss of spiritual meaning in contemporary education, while also offering solutions to develop an Islamic education system that is scientific, meaningful, and oriented towards the formation of perfect human beings.